PEMBERIAN SANKSI PELANGGARAN DISIPLIN APARATUR SIPIL NEGARA DILINGKUNGAN PEMERINTAH DAERAH KABUPATEN SIGI GUNA MENINGKATKAN PELAYANAN PUBLIK - Yusuf, Agustian (Katalogis, 2015)
This research aims to find out how the process of sanction given to civil servants in regional government of Sigi Regency, to find out abstacle in giving law it is empirical. The research setting was at Sigi Regency. The data used was primary and secondary data. The data were collected through interview and library study covering books, regulations, papers, previous studies, documents, etc. the data were analyzated qualitatively. The research result indicates that the smoothness of governance implementation and national depen on the perfectness of civil servants. Discipline in one of perfectness elements of being a civil servant. However, there are still many civil servants breaking rules. In the effort of increasing civil servants disciplinary, government has issued a policy namely government regulation no. 53 of 2010 concerning Civil Servants Disciplinary. Based on that, this research investigated how the process of sanction given to civil servants in regional government of Sigi Regency, to find out abstacle in giving sanction of discipline for civil servants. It was abtained that sanction giving in Sigi Government based on government regulation no. 53 of 2010, the sanction covering : (a) Light discipline sanction, (b) average discipline sanction, (c) Heavy discipline sanction, and those sanction are conducted by authorizated officer.